In the name of security : Governmentality apparatus in a multilingual mine in Arctic Finland - Strömmer, Maiju (Journal of Sociolinguistics, 2021)
This critical sociolinguistic study explores how mining work is governed in the name of security in a mine in Arctic Finland. Although the mining industry is dominated by multinational corporations, mines themselves tend to be concentrated in peripheries where a mobile and multilingual workforce is recruited. Mining is a high-risk business: industrial accidents and environmental damage can be severe. Discursive practices play a crucial role in risk management. In this study, the nexus of language, security, and production in mining work is analyzed by applying the Foucauldian concept of 'governmentality'. The data comprise ethnographic observations, work-related documents, and interviews collected onsite in 2018-2019. The analysis illustrates how security and production are interwoven in the mine's safety program that applies the neoliberal logic of responsibilization and disciplinary strategies of surveillance, supervision and regulations. On a broader level, this governmentality apparatus serves the state in securitizing its economy and population. peerReviewed